Analysis of the Influence of School Bench Facilities and Peer Interaction on Student Learning Motivation at Public High Schools in Malang City - Muhaimin, Muhammad Miko; Juharyanto, Juharyanto; Arifin, Imron (Proceedings Series of Educational Studies, 2024)
Schools play a crucial role in achieving quality education per national standards. Classrooms include physical aspects like aesthetics, seating arrangements, and lighting. Comfortable seating enhances learning, increases motivation, and boosts student achievements. Proper management of facilities, such as school benches, is essential for effective learning. Peer interaction also influences learning enthusiasm. Supportive friends boost motivation, while poorly behaved peers can diminish it. This descriptive quantitative study targets high school students in public schools across Malang City. Primary data was collected via Google Forms questionnaires. Stratified random sampling, using the Slovin formula at a 10% error rate, resulted in a sample of 100 respondents from a population of 10,884 students. Data analysis utilized multiple linear regression with IBM SPSS 24 for Windows, incorporating classical assumption tests, t-tests, F-tests, and R² tests. Keywords: school bench facilities; peer interaction; student learning motivation